Potentiation of anticonvulsant effect of phenytoin by celecoxib against maximum electroshock induced convulsions in albino rats - Nadeem, Mohammed Naseeruddin; Maqdoom, Maliha (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Epilepsy, a chronic neurological disorder affects more than 1% of world population. Despite the availability of a number of antiepileptics, refractoriness to them exists in approximately one third of cases worldwide. Induction of cycloxygenase and increased levels of proinflammatory meditators are seen in epilepsy. P-glycoprotein upregulation due to phenytoin was found to contribute to its pumping out of cell, leading to refractoriness to phenytoin therapy. Also, cycloxygenase-2 inhibitors were found to prevent P-glycoprotein upregulation. Since cycloxygenase-2 inhibition decreases levels of proinflammatory cytokines responsible for neuroinflammation, this study aims to evaluate anticonvulsant effect of celecoxib and also to investigate whether it potentiates the anticonvulsant effect of phenytoin. Methods: Maximum electroshock seizures (MES) were induced in Albino rats using electroconvulsiometer to evaluate tonic convulsions, identified by tonic hind limb extension (THLE) in rats. A delay in onset of THLE and a reduction in duration of THLE were taken as deciding parameters to ascertain anticonvulsive activity. Rats randomly divided into groups, received pretreatment with celecoxib at 3 doses (10, 20, 40 mg/kg), phenytoin (6.25 mg/kg), phenytoin (12.5 mg/kg) and combination of phenytoin (6.25 mg/kg) with celecoxib (ED50, i.e. 20 mg/kg), before inducing MES seizures and findings compared to control group. Results: Celecoxib (20 and 40 mg/kg) showed significant anticonvulsant effect by MES test. Also, its combination with phenytoin caused significant decrease in the duration of THLE when compared to phenytoin alone at the same dose. Conclusions: The results of this study indicate that celecoxib potentiates the anticonvulsant effect of phenytoin.